Efisiensi Teknis Usahatani Cabai Merah di Kecamatan Gunung Tujuh Kabupaten Kerinci - Adistya, Adilla; Saputra, Rido; Ramadhini, Khairunnisa (Universitas Batangahari Jambi, 2025)
Red chilies are one of the leading commodities in the horticultural crop subsector, and they have high economic value in Indonesia. Gunung Tujuh sub-district has the most significant harvest area and chili production in Kerinci Regency but does not yet have the highest level of productivity compared to other sub-districts. This research aims to analyze the efficiency level of red chili farming and identify the factors that influence it. The method used in this research is Stochastic Frontier Analysis with a Cobb-Douglass production function, which consists of two stages: the Ordinary Least Square (OLS) method and Maximum Likelihood Estimation (MLE). Data was collected from 34 red chili farmers selected using a simple random sampling method. The research results show that the average technical efficiency of red chili farming in Gunung Tujuh District is 0.84 or 84%, which means that red chili farming is at an efficient level. Based on the Cobb-Douglass production function analysis using the OLS method, three factors influence red chili production: land, organic fertilizer, and the number of workers. The results of this research can provide opportunities for farmers to continue to increase efficiency by up to 16%.